Geologia e mineralogia do pegmatito estanífero cascavel, mina bom futuro, Rondônia - Dias, Carlos Augusto Tavares [UNESP]; Leite Junior, Washington Barbosa [UNESP]; Muzzolon, Renato; Bettencourt, Jorge Silva (My University, 2013)
Bom Futuro Mine is located in the center-north region of Rondônia and it includes two hills named Palanqueta and Bom Futuro and the adjacent flattened areas as well. The main extraction areas of cassiterite occur in the surrounding placers of Bom Futuro hill, also in the primary deposits located in the hill itself. Such primary deposits are restricted to the bodies of pegmatite, which were formed in at least two distinct events. The Cascavel pegmatite belongs to the older event and it is composed by the main lenses and a swarm of dikes, veins and veinlets with NNW/35oENE general attitude. The bodies are massif or zoned and in the main lenses, three distinct zones were recognized under the form of sub-parallel layers among themselves and the walls of the lenses. From the wall to the roof there are: quartz and topaz zone, alkaline feldspar and Li-mica, and granitic zone. The main minerals of Cascavel pegmatite are quartz, alkaline feldspar, topaz, and Li-mica, and the subordinate minerals are cassiterite, sulfides (sphalerite, chalcopyrite, pyrite, galena, stannite), zircon, monazite, wolframite, uraninite, columbite-tantalite, and niobian rutile. The Cascavel pegmatite is a complex rare-element pegmatite belonging to LCT family and is spatially and temporally related to the late-stage peraluminous A-type granites of the Younger Granites of Rondônia.
Geology and mineralogy of rattlesnake pegmatite tinny, mine good future, Rondônia
Keywords: Bom Futuro Mine; Cassiterite; Pegmatite; Rondônia; Tin